Pengabdian Kepada Masyarakat Dalam Bidang Kesehatan Di Kelurahan Brebes - Insani, Arfita Ade Nur (FORDICATE, 2021)
Brebes Regency has a low vaccination achievement rate. Oneof the requirements for vaccination is to have normal blood pressure,therefore a blood pressure checking program is carried out so that thepublic can find out the latest blood pressure before vaccinating. Effortsto prevent covid-19 apart from vaccination are always having handsanitizers ready, in this case the researchers aim to distribute 25 bottlesof natural hand sanitizer spray as a form of community empowerment.The method of this activity is with public education regarding scientificrefreshment around covid-19 prevention, consultation on bloodpressure, and there is a science and technology simulation in itsapplication. The researcher is a student who is a member of the KSRPMI Campus Unit as a facilitator and was attended by 31 residents ofthe Brebes Village who took part in checking blood pressure andweight. The results of the activity were 14 people with high bloodpressure, 9 people with normal blood pressure, and 8 people with lowblood pressure. The average weight of the 31 people who took part inthis program was 56,48387 kg with an average weight in the age rangeof 6-13 years, namely 21 kg, age 21-25 years, 54.5 kg, age 31-40 years,namely 60.8 kg, the age range of 41-50 years is 61.2, and in the elderlyage range from 51-71 is 63.91 kg.